2017
DOI: 10.13057/biodiv/d180416
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Lack of differentiation within the bigeye tuna population of Indonesia

Abstract: Pertiwi NPD, Nugraha B, Kartika R, Sulistyaningsih RK, Jatmiko I, Sembiring A, Mahardini A, Cahyani NKD, Anggoro AW, Madduppa HH, Ambariyanto A, Barber PH, Mahardika GN. 2017. Short Communication: Lack of differentiation within the bigeye tuna population of Indonesia. Biodiversitas 18: 1406-1413. All highly migratory tuna and tuna-like species have vast feeding grounds and spawning grounds. Indonesia’s tuna catch is the largest in the world. However, genetic diversity in the population structure within parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
2
11
0
3
Order By: Relevance
“…This study showed a similar pattern as the bigeye tuna (Thunnus obesus) population in Indonesia which indicated one major clade of bigeye population and minor genetic differences between specific locations (Pertiwi et al 2017). Meanwhile, research conducted by Willette et al (2016) on Longtail Tuna in several locations in South China Sea, i.e.…”
Section: Phylogenetic Treesupporting
confidence: 67%
See 3 more Smart Citations
“…This study showed a similar pattern as the bigeye tuna (Thunnus obesus) population in Indonesia which indicated one major clade of bigeye population and minor genetic differences between specific locations (Pertiwi et al 2017). Meanwhile, research conducted by Willette et al (2016) on Longtail Tuna in several locations in South China Sea, i.e.…”
Section: Phylogenetic Treesupporting
confidence: 67%
“…In this study, Chelex method was used in DNA extraction method, because this method has been widely known as a simple, non-hazardous, and rapid genome DNA extraction process compared to other methods (Griese and Linder 1994). Chelex methods have been successfully used to extract good quality of DNA and commonly used methods of DNA extraction for genetic study, especially for commercial tuna such as Thunnus obesus (Pertiwi et al 2017), Thunnus albacares (Akbar et al 2014), Auxis thazard, Euthynnus affinis, Katsuwonus pelamis, Rastrelliger kanagurta, and Scomberomorus commerson (Jackson et al 2014). All of the sequences generated from the samples were deposited in the Genbank database (http://www.ncbi.nlm.nih.gov) with accession no.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Walsh et al (1991) menyebutkan bahwa metode ini banyak digunakan karena praktis, lebih cepat, dan tidak melibatkan pelarut organik serta tidak memerlukan banyak transfer tube untuk prosesnya sehingga mendapatkan genome sampel yang menjadi tujuan penelitian dibandingkan metode lainnya. Metode chelex juga telah berhasil diterapkan pada sampel Tuna (Jackson et al, 2014;Iranawati et al, 2016;Pertiwi et al, 2017;Malik et al, 2020).. .…”
Section: Ekstraksi Dnaunclassified